Economic Principles for Integrating Adaptation to Climate Change into Fiscal Policy - Bellon, Matthieu (Staff Climate Notes; Staff Climate Note ;, 2022)
Adaptation to climate change is a necessity for advanced and developing economies alike. Policymakers face the challenge of facilitating this transition. This Note argues that adaptation to climate change should be part of a holistic development strategy involving both private and public sector responses. Governments can prioritize public investment in adaptation programs with positive externalities, address market imperfections and policies that make private adaptation inefficient, and mobilize revenues for, and distribute the benefits of, adaptation. Although the choice of what should be done and at what cost ultimately depends on each society's preferences, economic theory provides a useful framework to maximize the impact of public spending. Cost-benefit analysis, complemented by the analysis of distributional effects, can be used to prioritize adaptation programs as well as all other development programs to promote an efficient and just transition to a changed climate. While compensations may be needed to offset damages that are either impossible or too expensive to abate, subsidies for adaptation require careful calibration to prevent excessive risk taking.